A study on cercarial dermatitis in Khuzestan province, south western Iran - Essalat Mostafa; Farahnak Ali (BMC, 2003)
Abstract Background Cercarial dermatitis' or swimmer's itch' is an itchy inflammatory response to the penetration of the skin by non-human schistosome parasites. In the hot season, (May to September) in Khuzestan province in the south west of Iran, swimming in canals and agriculture activities in swampy areas are common. This survey was made on people from villages north of Ahwaz city in south west Iran, to estimate cercarial dermatitis in this region. Methods 2000 people were observed for clinical signs of cercarial dermatitis. Also 2000 Lymnaea gedrosiana snails were collected from agriculture canals and examined for animal schistosome cercariae during 1998-2000. Results From this survey 1.1% of people had pruritic maculopapular rash on their feet, hands or other parts of body. From the total of examined snails, 2.4% were found to be infected with bird schistosome cercariae including Trichobilharzia species. Conclusion Cercarial dermatitis could be a health problem in this area. This is the first report of cercarial dermatitis from this region of Iran.